Age-based growth variation of green-blotched parrotfish scarus quoyi in the Southern Philippine Seas - Elumba, Merlene; Mata, May Anne E.; Abpi, Muhammad Monzer; Nañola, Cleto L., Jr. (2019)
Age structures of Scarus quoyi populations among three different bays (Davao Gulf, Pujada Bay, and Sarangani Bay) within a spanning distance of ~300 km in the southern Philippine seas were estimated by analyzing sagittal otoliths of 264 individuals. Growth from each study location was fitted using von Bertalanffy growth functions (VBGF) and the derived size-at-age trajectories for the three populations were compared. The 95% confidence interval ellipses around least squares estimate of K and L∞ showed non-overlapping regions, indicating strong differences among the examined populations. The difference in growths among Davao Gulf (K=1.00941), Pujada Bay (K=1.35561), and Sarangani Bay (K=0.98114) populations are statistically significant. The Davao Gulf population achieved larger mean asymptotic size than populations from Pujada Bay and Sarangani Bay. These variations could possibly suggest that growth rate differences are related to monsoon-driven seasonal changes, level of nutrient load and food availability, and habitat structure – including the type of substrate on the reef.
Keywords: Parrotfishes